Raptor biomedicine III: including bibliography of birds of prey - Lumeij, Johannes T. (Zoological Education Network, 2000)
pt. I. Microbiology [ch.] 1-5 -- pt. II. Parasitology [ch.] 6-11 -- pt. III. Pathology and poisoning [ch.] 12-15 -- pt. IV. Medicine and surgery [ch.] 16-22 -- pt. V. Veterinary management and captive breeding [ch.] 23-27 -- pt. VI. Rehabilitation and telemetry [ch.] 28-31 -- pt. VII. Resolution [ch.] 32 -- pt. VIII. Bibliography [ch.] 33 -- Appendices -- Index.